Pastoralism: A sustainable and nature-positive production system - International Livestock Research Institute; International Union for Conservation of Nature; World Wide Fund for Nature; Food and Agriculture Organization of the United Nations; United Nations Environment Programme; International Land Coalition (International Livestock Research Institute, 2021)
This film shows how pastoralism is a sustainable and nature-positive production system in Italy, contributing to economies, societies and the environment. Filmed in three different areas of the country - Sardinia, the Italian Alps, and Abruzzo - it brings together the opinions and views of different stakeholders on benefits, challenges and opportunities, including for the future. Filmed by Marco Buemi Website: http://www.marcobuemi.com Directed by Fiona Flintan, Marco Buemi and Cristina Ghinassi